Fluoride and phosphate release from carbonate-rich fluorapatite during managed aquifer recharge - Schafer, David; Donn, Michael; Atteia, Olivier; Sun, Jing; MacRae, Colin; Raven, Mark; Pejcic, Bobby; Prommer, Henning (Journal of hydrology (Amsterdam), 2018)
[Display omitted] •Fluoride and phosphate were mobilised during a MAR trial with deionised wastewater.•CFA was identified as the source of fluoride and phosphate.•Lab experiments with CFA rich nodules reproduced the field-observed behaviour.•CFA and FAP are ubiquitous in many aquifer settings.•F mobilisation risks need to be evaluated prior to MAR with low ionic strength water. Managed aquifer recharge (MAR) is increasingly used as a water management tool to enhance water availability and to improve water quality. Until now, however, the risk of fluoride release during MAR with low ionic strength injectate has not been recognised or examined. In this study we analyse and report the mobilisation of fluoride (up to 58 µM) and filterable reactive phosphorus (FRP) (up to 55 µM) during a field groundwater replenishment experiment in which highly treated, deionised wastewater (average TDS 33 mg/L) was injected into a siliciclastic Cretaceous aquifer. In the field experiment, maximum concentrations, which coincided with a rise in pH, exceeded background groundwater concentrations by an average factor of 3.6 for fluoride and 24 for FRP. The combined results from the field experiment, a detailed mineralogical characterisation and geochemical modelling suggested carbonate-rich fluorapatite (CFA: Ca10(PO4)5(CO3,F)F2) to be the most likely source of fluoride and phosphate release. An anoxic batch experiment with powdered CFA-rich nodules sourced from the target aquifer and aqueous solutions of successively decreasing ionic strength closely replicated the field-observed fluoride and phosphate behaviour. Based on the laboratory experiment and geochemical modelling, we hypothesise that the release of fluoride and phosphate results from the incongruent dissolution of CFA and the simultaneous formation of a depleted layer that has hydrated di-basic calcium phosphate (CaHPO4·nH2O) composition at the CFA-water interface. Disequilibrium caused by calcium removal following breakthrough of the deionised injectate triggered the release of fluoride and phosphate. Given the increasing use of highly treated, deionised water for MAR and the ubiquitous presence of CFA and fluorapatite (Ca10(PO4)6F2) in aquifer settings worldwide, the risk of fluoride and phosphate release needs to be considered in the MAR design process.